How Sophisticated is Green Banking in Poland and Romania? A Case Study of Bank Offers - SIEMIONEK-RUSKAŃ, Małgorzata; FANEA-IVANOVICI, Mina (Journal of Environmental Management and Tourism, 2023)
The role of commercial banks in promoting sustainable development goals in Europe has gained ground recently. The momentum is also due to the Green Deal context. Their activity has shifted towards the achievement of such goals by getting involved in environmental projects or by raising awareness about sustainability. Their endeavors can also be directly reflected in the products and services they provide to the population and businesses. This is how commercial banks have taken up the role of educating the public towards sustainability and sustainable development goals. The aim of this paper is to investigate the green banking products and services of the largest five banks, by the number of clients, in Poland in Romania. A descriptive qualitative analysis is used to estimate the degree of sophistication of green banking products and services in the two countries.